2018
DOI: 10.1155/2018/8324093
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Endarterectomy Effect on Choroidal Thickness: One-Year Follow-Up

Abstract: Purpose To evaluate the change in choroidal thickness after carotid artery endarterectomy (CEA) in patients without retinal pathology. Methods A prospective series of patients who underwent CEA at the Tel Aviv Medical Center. Spectral domain optical coherence tomography (SD-OCT) was performed one day before the CEA and at least 6 months after. Data included medical history, smoking history, percentage of carotid stenosis before and after CEA, best-corrected visual acuity (BCVA), central macular thickness (CMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In contrast, Rabina et al, based on a group of 8 patients with unilateral severe ICAS undergoing carotid endarterectomy, did not find any significant differences in SFCT between 6 and 14 months after surgery. e authors speculated that choroidal blood supplying the retina was sufficient despite the severe internal carotid stenosis in patients without ischaemic ocular syndrome signs due to preserved ophthalmic artery blood flow [27]. However, the study group was relatively small and predominantly male, and the participants were older.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, Rabina et al, based on a group of 8 patients with unilateral severe ICAS undergoing carotid endarterectomy, did not find any significant differences in SFCT between 6 and 14 months after surgery. e authors speculated that choroidal blood supplying the retina was sufficient despite the severe internal carotid stenosis in patients without ischaemic ocular syndrome signs due to preserved ophthalmic artery blood flow [27]. However, the study group was relatively small and predominantly male, and the participants were older.…”
Section: Discussionmentioning
confidence: 97%
“…However, the study group was relatively small and predominantly male, and the participants were older. Importantly, all of them were hypertensive, which could have potentially affected their results [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding CT, there is controversial evidence in the literature too, with reports disclosing significant choroidal thinning or preserved CT ( Sayin et al, 2015 ; Rabina et al, 2018 ). In our study, CT resulted significantly lower in CAS eyes.…”
Section: Discussionmentioning
confidence: 99%
“…The last study suggested that SFCT may perform well in choosing the optimal schedule for carotid surgery. Changes in SFCT before and after carotid endarterectomy (CEA) has been the topic of four small series (Lareyre et al 2018; Rabina et al 2018; Akca Bayar et al 2020; Krytkowska et al 2020), again with partly contradictory results and only one of these with control subjects (Akca Bayar et al 2020).…”
Section: Introductionmentioning
confidence: 99%